2022
DOI: 10.1177/09564624221125356
|View full text |Cite
|
Sign up to set email alerts
|

Weight changes after first-line antiretroviral initiation in a cohort of HIV-positive patients in Southern Spain (CAPOTA study)

Abstract: Background Obesity among persons living with HIV (PLWH) has increased and weight gain after antiretroviral therapy (ART) can lead to metabolic disorders and impact survival. Our objective was to analyze weight and metabolic changes in HIV näive patients after 48 weeks of ART. Methods Observational, retrospective, multicentered cohort study comprising naïve-patients who started tenofovir alafenamide/emtricitabine/elvitegravir/cobicistat (TAF/FTC/EVG/c) or abacavir/lamivudine/dolutegravir (ABC/3TC/DTG), with no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Similar to the general population, people living with HIV are exhibiting a continuous growth in the trends of obesity. Studying obesity mechanisms and prevention in people with HIV is challenging due to the complex nature of obesity itself, and the proven contribution of some first-line antiretrovirals (ARVs) in promoting weight gain in people with HIV [1,2]. Pooled analysis from the USA and Canada with over 14 000 individuals with HIV demonstrated that 22% of normal-weight patients became overweight, and 18% of overweight patients became obese over 3 years after ARV initiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the general population, people living with HIV are exhibiting a continuous growth in the trends of obesity. Studying obesity mechanisms and prevention in people with HIV is challenging due to the complex nature of obesity itself, and the proven contribution of some first-line antiretrovirals (ARVs) in promoting weight gain in people with HIV [1,2]. Pooled analysis from the USA and Canada with over 14 000 individuals with HIV demonstrated that 22% of normal-weight patients became overweight, and 18% of overweight patients became obese over 3 years after ARV initiation [3].…”
Section: Introductionmentioning
confidence: 99%